Volatile composition and aromatic attributes of wine made with Vitisvinifera L.cv Cabernet Sauvignon grapes in the Xinjiang region of China: effect of different commercial yeasts. Issue 1 (1st January 2018) - Duan, Wei-Peng; Zhu, Bao-Qing; Song, Ru-Ru; Zhang, Bo; Lan, Yi-Bin; Zhu, Xia; Duan, Chang-Qing; Han, Shun-Yu
ABSTRACT: The Xinjiang region is a major grape- and wine-production area in China, but the region's notably high temperatures in the summer and year-round intense sun exposure play negative roles in the aroma, complexity, and elegance of Cabernet Sauvignon wine. In this study, Cabernet Sauvignon grapes harvested in this region were fermented on an industrial scale using four commercial yeast strains (L2323, D254, RVA, and CECA) and spontaneous yeast (NF). The results showed that a total of 123 volatile compounds were detected and 15 volatile compounds significantly contributed their flavor notes to the wine's overall aroma. The use of RVA and CECA strains resulted in wine with higher concentrations of higher alcohols, terpenes and norisoprenoids. However, the D254-fermented wine showed high level of esters and carbonyl compounds. Wine fermented with the L2323 and D254 strain possessed a stronger fruity aroma, whereas the RVA strain enhanced the herbaceous, chemical, and fatty aromas in wine. Principal component analysis revealed that a significant aromatic feature difference was observed in these wines after alcoholic and malolactic fermentation. The use of different commercial yeast strains altered the aromatic profile of Cabernet Sauvignon wine.